Spatio-Temporal Analysis of the Pre-Earthquake Disturbances in the Ionosphere before Ten Earthquakes with Magnitudes Greater than Mw 5.0 - Karatay, Secil; Arikan, Feza; Pirti, Atinc (Springer Science and Business Media LLC, 2024)
Abstract
This study analyzes the variations in Total Electron Content (TEC) to perform a spatio-temporal evaluation of pre-earthquake disturbances in the ionosphere in order to characterize anomalies occurred before the major earthquakes using Differential Rate Of TEC (DROT) algorithm. By employing the DROT technique, significant TEC oscillations have observed 1–5 days before the earthquakes. The temporal approach showed a higher frequency of oscillations on the day immediately preceding the event. The spatial approach showed clustering around 500 km from the epicenter at most. Finally, the approach depending on the magnitude of the earthquake showed that large-scale ionospheric disturbances occurred before the earthquakes with magnitude greater than Mw 5.6.